Characteristics of the Russian population of patients with coronary artery disease or peripheral artery disease in the XATOA registry - V. S. Arakelyan; A. D. Erlikh; N. Sh. Amirov; E. Dubar; K. Vogtlaender; S. Debus (Рациональная фармакотерапия в кардиологии)
Aim. To analyze demographic, anamnestic and clinical parameters in subjects with coronary artery disease (CAD) or peripheral artery disease (PAD) included in the XATOA study from Russian centers and to compare them with the total population of the international registry.Material and methods. XATOA study is an international, multicenter, prospective registry, where characteristics of patients receiving dual pathway inhibition therapy with rivaroxaban 2,5 mg twice a day and low-dose acetylsalicylic acid (ASA) daily were analyzed. The secondary endpoint of the study was to assess clinical outcomes and bleeding rates in real world setting.This analysis was based on the comparison of indicators presented in tables of descriptive statistics from the XATOA study database for subjects from Russia and the general study database respectively. The methodology of this sub-analysis is descriptive only and does not imply any statistical difference assessment.Results. The Russian population included 795 subjects: 232 (29.2%) subjects with CAD; 293 (36.9%) subjects with PAD and 270 (34.0%) subjects with both. The average follow-up period was 14.4 months. The most common antithrombotic treatment regimen for patients with CAD or PAD prior enrollment in the registry was ASA monotherapy (81.3%); ACE inhibitors/ARBs were prescribed in 61.8%, lipid-l owering therapy in 68.9%. After the enrollment and prescription of rivaroxaban 2.5 mg BID + ASA, the incidence of myocardial infarction, stroke or cardio-v ascular death in subjects in the Russian Federation remained at 1.9%, and the incidence of major adverse limb events (MALE) at 0.8%, which corresponds to the results obtained in the COMPASS randomized controlled trial. Major bleeding was reported in 1 subject (<0.1%). Adherence to the therapy among subjects in the Russian Federation amounted to 89.8%.Conclusion. Despite the increased incidence of concomitant diseases and insufficient use of routine cardiovascular therapy in subjects with CAD or PAD in the Russian Federation, the ischemic complications rate remains at a relatively low level while using antithrombotic treatment with rivaroxaban 2.5 mg twice a day + ASA 100 mg a day.